Catching Up to the CCSS: A Principal Navigates Out-of-Subject Instructional Leadership. (September 2015) - Quebec Fuentes, Sarah; Switzer, J. Matt; Jimerson, Jo Beth
This case provides principals and principal licensure candidates an opportunity to delve into the nuances of supervising teachers in content areas, which may be unfamiliar, and to explore strategies for increasing knowledge about the structures and emphases of the Common Core State Standards (CCSS). The case presents issues related to curriculum, instructional leadership strategies, professional learning networks, and supervision and evaluation of teachers. It can also be a springboard for connecting principals and licensure candidates with resources to deepen familiarity with best practice research in mathematics instruction.